A novel instructional activity using neuroscience core concepts as a pedagogical tool to improve contextualization of primary research articles - Hannah, Rachael M.; Schaefer, Jennifer E. (Frontiers in Education, 2025)
Reading primary literature is beneficial for STEM students but, as novice learners, they struggle to integrate research into larger knowledge frameworks and to apply findings beyond a narrow scope. Best practices for teaching primary scientific literature often emphasize development of conceptual knowledge, scientific process competency, or affective goals rather than the goal of contextualizing research. We hypothesized that a novel pedagogical intervention leveraging neuroscience core concepts would improve students’: (1) ability to connect primary research articles to broader knowledge contexts, and (2) metacognitive strategies for contextualizing primary research articles. Preliminary qualitative scoring indicated that the intervention improved students’ linking of primary research articles to larger conceptual frameworks and that the intervention was more effective when embedded in ongoing pedagogical use of core concepts. Student reflections on their learning processes indicated that they primarily leveraged core concepts for metacognitive declarative knowledge and metacognitive information management strategies. Given that core concepts are published for a variety of STEM fields, findings are of interest to a range of STEM instructors. This work builds on a growing collective effort to implement disciplinary core concepts into accessible, scalable teaching methods, emphasizing engagement with primary scientific literature.